2020
DOI: 10.1111/1471-0528.16395
|View full text |Cite
|
Sign up to set email alerts
|

The use of host cell DNA methylation analysis in the detection and management of women with advanced cervical intraepithelial neoplasia: a review

Abstract: This paper briefly reviews the role of hypermethylation of host cell genes in cervical carcinogenesis and discusses potential clinical applications of methylation analysis in the management of highrisk HPV (hrHPV) -positive women. We argue that methylation assays can be used: 1. for primary triage of hrHPV-positive women to detect cervical cancer and advanced cervical intraepithelial neoplasia (CIN); 2. as secondary triage for women with minor cytological abnormalities to identify those with the highest risk o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 92 publications
(232 reference statements)
1
64
0
Order By: Relevance
“…Major benefits of methylation such as high reproducibility, sensitivity and specificity have been confirmed by growing evidence. 3 In summary, the study by Loopik et al was useful in focusing on CS for the triage of hrHPV-positive CS, and reinforcing the need to reduce diagnostic delay and loss to follow-up. 1 Challenges remain because of the low sensitivity for detecting CIN2+ and the limitation of descriptive studies lacking accuracy comparisons with clinically common strategies.…”
Section: Sirmentioning
confidence: 96%
See 3 more Smart Citations
“…Major benefits of methylation such as high reproducibility, sensitivity and specificity have been confirmed by growing evidence. 3 In summary, the study by Loopik et al was useful in focusing on CS for the triage of hrHPV-positive CS, and reinforcing the need to reduce diagnostic delay and loss to follow-up. 1 Challenges remain because of the low sensitivity for detecting CIN2+ and the limitation of descriptive studies lacking accuracy comparisons with clinically common strategies.…”
Section: Sirmentioning
confidence: 96%
“…Clinically, pregnant women with the more severe COVID-19 infection appear to prefer delivery by caesarean delivery rather than vaginal birth. [2][3][4] Therefore, it is possible that any beneficial effects of caesarean birth in reducing transmission of COVID-19 might not be apparent because the severity of COVID-19 infection was greater in these women. This selective bias would weaken the conclusions of current studies.…”
Section: Sirmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA methylation in genes and HPV testing have been investigated as triage methods to improve risk stratification of HR-HPV positive women. Studies summarizing the performance of DNA methylation in CIN2 and CIN3 detection have reported significantly higher DNA methylation in CIN2+ and CIN3+ compared to ≤ CIN1 [ 10 , 14 ]. We previously reported that aberrant methylation at DMRs that regulate the expression of imprinted genes including Insulin-like Growth Factor 2 (which expresses IGF2, a potent mitogen), Paternally Expressed Gene 1/Mesoderm-Specific Transcript ( PEG1/MEST ) and Paternally Expressed Gene 3 ( PEG3 ) were independent predictors of CIN2/3 and ICC in a cross-sectional study of Tanzanian women with CIN and ICC [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%